2014
DOI: 10.1021/mp500174p
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Phospholipase A2 Receptor in Liposome Drug Delivery in Prostate Cancer Cells

Abstract: The M-type phospholipase A2 receptor (PLA2R1) is a member of the C-type lectin superfamily and can internalize secreted phospholipase A2 (sPLA2) via endocytosis in non-cancer cells. sPLA2 itself was recently shown to be overexpressed in prostate tumors and to be a possible mediator of metastasis; however, little is known about the expression of PLA2R1 or its function in prostate cancers. Thus, we examined PLA2R1 expression in primary prostate cells (PCS-440-010) and human prostate cancer cells (LNCaP, DU-145, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Analysis of zeta potential and size indicated that these nanoparticles would be functional for clinical application, and the activity of these formulations were verified in vitro . It is not surprising that SSL-IPA-3 were not as effective as free IPA-3 in vitro and in vivo , as this is commonly seen in many studies, including those reported from our own laboratory 16, 22, 29 . What was surprising was that the effect of SSL-IPA-3 was shown to be cell type-dependent and mediated by the level of expression of PAK-1.…”
Section: Discussionmentioning
confidence: 51%
“…Analysis of zeta potential and size indicated that these nanoparticles would be functional for clinical application, and the activity of these formulations were verified in vitro . It is not surprising that SSL-IPA-3 were not as effective as free IPA-3 in vitro and in vivo , as this is commonly seen in many studies, including those reported from our own laboratory 16, 22, 29 . What was surprising was that the effect of SSL-IPA-3 was shown to be cell type-dependent and mediated by the level of expression of PAK-1.…”
Section: Discussionmentioning
confidence: 51%
“…PLA2R1 expression was found decreased in leukaemia, mammary, renal and thyroid cancers [ 9 , 12 – 15 ]. While the receptor is down-regulated in these cancers, significant up-regulation of PLA2R1 was described in the prostate cancer cell lines PC-3 and DU-145 in comparison to normal prostate cells [ 16 ]. High expression of PLA2R1 was also identified in ovarian carcinoma effusions, human leukemic blasts and dermatofibrosarcoma [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence liposome formulation. Pegylated liposomes were prepared as previously described 249 [41,42]. Briefly, formulations were generated according to a ratio of 10 µmol DPPC, injected into each growing follicle using a double-channel injection system as previously described [4,44].…”
Section: Liposome Nanoparticle Preparation and Characterizationmentioning
confidence: 99%